2017
DOI: 10.3945/ajcn.116.150995
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-based intervention intended to stop obesity in preschool-aged children: the MINISTOP randomized controlled trial ,

Abstract: Background: Traditional obesity prevention programs are time-and cost-intensive. Mobile phone technology has been successful in changing behaviors and managing weight; however, to our knowledge, its potential in young children has yet to be examined. Objective: We assessed the effectiveness of a mobile health (mHealth) obesity prevention program on body fat, dietary habits, and physical activity in healthy Swedish children aged 4.5 y. Design: From 2014 to 2015, 315 children were randomly assigned to an interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
228
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(237 citation statements)
references
References 40 publications
9
228
0
Order By: Relevance
“…Similarly, Lissner et al found that effects of the Identification and prevention of Dietary‐ and lifestyle‐induced health EFfects In Children and infantS (IDEFICS) intervention—a school‐ and community‐level obesity intervention in eight European countries focused on children 2 to 10 years of age—on weight status were only observed among children who were overweight at the start of the intervention. Similar findings were reported by Nyström et al from a mobile‐based intervention among preschool‐aged children in Sweden, in which children with a higher fat mass index at baseline benefitted more from the intervention than children with a normal weight.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, Lissner et al found that effects of the Identification and prevention of Dietary‐ and lifestyle‐induced health EFfects In Children and infantS (IDEFICS) intervention—a school‐ and community‐level obesity intervention in eight European countries focused on children 2 to 10 years of age—on weight status were only observed among children who were overweight at the start of the intervention. Similar findings were reported by Nyström et al from a mobile‐based intervention among preschool‐aged children in Sweden, in which children with a higher fat mass index at baseline benefitted more from the intervention than children with a normal weight.…”
Section: Introductionsupporting
confidence: 86%
“…Findings of the larger study indicate that children exposed to the new food package (ie, those enrolled in WIC after October 1, 2009) have healthier (ie, further from the overweight category) growth trajectories and a lower obesity prevalence at age 4 years than those exposed to the old food package . However, since other studies have suggested that children with overweight or obesity may benefit the most from obesity interventions, our objective was to investigate whether the effect of the new WIC food package, compared with the old, on obesity outcomes varied by children's initial weight status. We hypothesized that exposure to the new WIC food package, compared with the old, is associated with the greatest reduction in obesity among children with the highest initial weight status.…”
Section: Introductionmentioning
confidence: 99%
“…The WellWe intervention was developed in a multidisciplinary team, with representatives from the fields of nursing, medicine, nutrition, physical activity, information technology and graphic design. The development of the WellWe application followed a typical iterative development process intended for games and applications (Novak, 2012) and participatory design principles to ensure sustainable implementation of the WellWe intervention (McIntyre, 2008). The development process consisted of several steps; a more detailed description of the development process is reported in Pakarinen et al (2017).…”
Section: Interventionmentioning
confidence: 99%
“…However, there is also conflicting evidence. A recent RCT study on a mobile health intervention aimed at preventing obesity among 4‐year‐old children (the Ministop) found no difference between the intervention and control group with respect to changes in the fat mass index (Nyström et al., ). These previous digital health interventions were targeted at parents only and to our understanding, there are no previous studies on family‐centred digital health interventions intended for both parents and their small children.…”
Section: Introductionmentioning
confidence: 99%
“…[1] To date, one of the few studies using a parent-focused mHealth intervention to target early childhood audiences, reported sustained parental engagement with the smartphone app and improvement in certain diet and physical activity behaviors. [2] Among a wider age range of children, evidence suggests that electronic interventions on obesity can positively affect dietary and physical activity behaviors. [3,4] Interventions focused on early childhood are promising, in part, because early eating and activity habits can translate into adolescence and even adulthood, making early childhood a crucial time to establish healthy habits.…”
Section: Introductionmentioning
confidence: 99%